2013
DOI: 10.1158/1055-9965.epi-13-0328
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms in Genes Encoding for CC Chemokines were Not Associated with the Risk of Non-Hodgkin Lymphoma

Abstract: Background Chemokines play a pivotal role in immune regulation and response, and previous studies suggest an association between immune deficiency and Non-Hodgkin lymphoma (NHL). Methods We evaluated the association between NHL and polymorphisms in 18 genes (CCL1, CCL2, CCL5, CCL7, CCL8, CCL11, CCL13, CCL18, CCL20, CCL24, CCL26, CCR1, CCR3, CCR4, CCR6, CCR7, CCR8 and CCR9) encoding for the CC chemokines using data from a population-based case-control study of NHL conducted in Connecticut women. Results CCR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In agreement, mRNA levels in FL cells did not differ from those of their normal counterparts (32,(84)(85)(86)(87). The genetic variants of CCR7 rs2023906, rs2290065, rs3136685, and rs588019, were not associated with differential expression or with clinical course in FL (50). The fact that CCR7 is not prominently found in most FL suggests that it has a limited role in the pathophysiology of this lymphoma, which is supported by recent evidence.…”
Section: Follicular Lymphoma (Fl)supporting
confidence: 76%
See 1 more Smart Citation
“…In agreement, mRNA levels in FL cells did not differ from those of their normal counterparts (32,(84)(85)(86)(87). The genetic variants of CCR7 rs2023906, rs2290065, rs3136685, and rs588019, were not associated with differential expression or with clinical course in FL (50). The fact that CCR7 is not prominently found in most FL suggests that it has a limited role in the pathophysiology of this lymphoma, which is supported by recent evidence.…”
Section: Follicular Lymphoma (Fl)supporting
confidence: 76%
“…In CLL, genetic factors or polymorphisms involved in the overexpression of CCR7 remain uncovered but one singlenucleotide polymorphism (SNP) in the CCR7 gene was strongly associated with the risk of acquiring CLL. Out of 6 tested SNPs (including rs11574665, rs2023906, rs2290065, rs3136685, rs3136687, and rs588019) (49,50), the major G allele in the SNP rs3136687, which is located at the first intron and is in linkage disequilibrium with rs11574665, was associated with a higher risk towards CLL whereas the minor A allele resulted in a protective effect (49). The authors found no differences in CCR7 expression for such allelic variants.…”
Section: Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 95%
“…This would thereby block the vicious cycle that leads to psoriasis. However, the difference value of CCR6 before and after phototherapy treatment and the PASI difference value were negatively correlated, so it cannot be ruled out that the expression level of CCR6 in peripheral blood might also be a concomitant phenomenon or be a process related to disease development (Chen et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, recent evidence supports the hypothesis that both the inner genetic background of leukemic cells and/or environment factors facilitate CCR7 over-expression. To our knowledge, no potential CCR7 gene mutations affecting transcription have been reported in CLL but one single-nucleotide polymorphism (SNP) in this gene was strongly associated with CLL risk (71,82). Enjuanes et al (81) found that the minor allele in the SNP rs3136687 (intron 1) resulted in a protective effect for the risk of CLL, although no CCR7 expression differences were observed for such allelic variants.…”
Section: Mechanisms Underlying Ccr7 Expression In Cllmentioning
confidence: 99%
“…Nonetheless, recent evidence supports the hypothesis that both the inner genetic background of leukemic cells and/or environment factors facilitate CCR7 over-expression. To our knowledge, no potential CCR7 gene mutations affecting transcription have been reported in CLL but one single-nucleotide polymorphism (SNP) in this gene was strongly associated with CLL risk ( 71 , 82 ). Enjuanes et al.…”
Section: Cllmentioning
confidence: 99%